2016
DOI: 10.3109/13880209.2016.1173066
|View full text |Cite
|
Sign up to set email alerts
|

Anti-rheumatic activity ofAnanas comosusfruit peel extract in a complete Freund’s adjuvant rat model

Abstract: Context: Rheumatoid arthritis is a chronic, autoimmune and systemic inflammatory disease, which targets synovial joints leading to joint destruction mediated in part by migration of inflammatory cells into the synovial tissue. Objective: The present study evaluates the anti-rheumatic effect of a methanol extract of Ananas comosus (L.) Merr. (Bromeliaceae) peel in rats. Materials and methods: Anti-rheumatic activity of crude extract of peels of A. comosus in complete Freund's induced arthritis model in rats was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 23 publications
2
18
0
1
Order By: Relevance
“…The model equation was used to estimate the best experimental conditions, and to describe the interaction between the assessed parameters (Eqn. 1): [1] where Y is the response; j and k are the linear and quadratic coefficients, respectively, Xi and Xj are the uncoded independent parameters, l represents the number of studied and optimized variables in the experiment, β0 is a constant coefficient; βj, βjj and βjk are the interaction coefficients of linear, quadratic and second−order terms, respectively; and finally, ε is the error.…”
Section: Response Surface Methodology (Rsm) For the Uae Of Ppmentioning
confidence: 99%
See 2 more Smart Citations
“…The model equation was used to estimate the best experimental conditions, and to describe the interaction between the assessed parameters (Eqn. 1): [1] where Y is the response; j and k are the linear and quadratic coefficients, respectively, Xi and Xj are the uncoded independent parameters, l represents the number of studied and optimized variables in the experiment, β0 is a constant coefficient; βj, βjj and βjk are the interaction coefficients of linear, quadratic and second−order terms, respectively; and finally, ε is the error.…”
Section: Response Surface Methodology (Rsm) For the Uae Of Ppmentioning
confidence: 99%
“…Ananas comosus (L.) Merr, otherwise known 'nanas' in Southeast Asia or pineapple in English, is a plant from the Bromeliaceae family that is native to the Central and South Americas [1] and grows well in tropical and subtropical regions, such as Thailand, Malaysia, Philippines, India, China, Hawaii, South Africa and Kenya. Its yellow, sweet−flavored flesh contains an appreciably high content of carotenoid, which causes the pulp to have the same hue as the peels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These polyphenolic compounds exhibit their antioxidant potential [19]. Methanolic extract of AC fruit peel also shows anti-rheumatic activity [20]. It has been reported that AC peel extract has antioxidative and antibacterial potential, which can be useful in food applications [9, 21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Bromelain decreased swelling and pain by inhibition of cyclooxigenase-2 (COX-2) and prostaglandin E2 (PGE2) expression in rheumatoid arthritis. It ameliorated the inflammation by protection of cartilage from damage in rheumatoid arthritis at a dose 100 and 500 mg/kg [49]. In an experiment, it showed a significant effect on knee treatment suffering in osteoarthritis at a dose 10 mg/kg [50].…”
Section: Bromelainmentioning
confidence: 93%